THE GRAMMATICAL-SEMANTIC PROPERETIES OF ENGLISH MEDIO-PASSIVES: HOW NECESSARY ARE THEY FOR EFL LEARNERS IN MULTILINGUAL SOCIETIES? - Jufrizal Jufrizal (Universitas Negeri Padang, 2016)
Although learning a foreign language means learning to communicate in the language, it does not mean that to study and to understand the grammatical-semantic features of the learnt language are not essential. Most EFL learners in Indonesia, for instance, have academically known the grammatical-semantic properties of English actives and passives. However, it is assumed that not all EFL learners in multilingual societies academically know and cognitively understand the grammatical-semantic properties of one more phenomenon of English voice so called medio-passive constructions. Medio-passive constructions are grammatically constructed in active forms, but they are semantically understood as passive ones. This paper, which is derived and further developed based on a research report conducted in 2012 (Mukhaiyar an Jufrizal, 2012), particularly discusses: (i) the grammatical-semantic properties of English medio-passive constructions; and (ii) how they are academically and communicatively necessary for EFL learners in multilingual societies, as in Indonesia. The data presented in this paper are selected from those collected in a research conducted in 2012 and added with the relevant ones collected along with the writer did his activities in teaching English at S1 and S2 study programs of Universitas Negeri Padang. The analysis toward the data and its discussion are based on the relevant theories of linguistic typology of voice systems of English and foreign language learning, especially learning EFL for multi-lingual societies.